2018
DOI: 10.1093/nar/gky881
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic network approach for the modelling of genomic sub-complexes in multi-segmented viruses

Abstract: Viruses with segmented genomes, including pathogens such as influenza virus, Rotavirus and Bluetongue virus (BTV), face the collective challenge of packaging their genetic material in terms of the correct number and types of segments. Here we develop a novel network approach to predict RNA–RNA interactions between different genomic segments. Experimental data on RNA complex formation in the multi-segmented BTV genome are used to establish proof-of-concept of this technique. In particular, we show that trans in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…It is highly likely that RNA segments interact with each other in a sequential manner prior to the packaging of the RNA complex into the capsid (1, 5, 15). In a recent report, we showed that RNA segment assortment is based mainly on RNA-RNA interactions via specific sequences (32). It is possible that VP6 is also actively involved in assortment, but our current data do not support this notion.…”
Section: Discussionmentioning
confidence: 99%
“…It is highly likely that RNA segments interact with each other in a sequential manner prior to the packaging of the RNA complex into the capsid (1, 5, 15). In a recent report, we showed that RNA segment assortment is based mainly on RNA-RNA interactions via specific sequences (32). It is possible that VP6 is also actively involved in assortment, but our current data do not support this notion.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, while the loss of function of one of the mRNA S10-S6 interactions caused by substitutions could be recovered by compensatory substitutions, the same was not true for a second interaction that was tested. The latter result suggests that localized changes can have global effects in a segment that lead to interference with other parts of the interactive network [37]. Additional functionally relevant BTV segment interactions have also been reported.…”
Section: Orbivirusesmentioning
confidence: 98%
“…Recently, a computational approach was used to predict a sequential assembly pathway to describe mRNA complex formation for segments S6 through S10 (Figure 3B) [37]. Briefly, the approach involved first identifying predicted ssRNA regions in each mRNA and then assessing potential tRRIs between these regions.…”
Section: Orbivirusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Reoviridae +RNA sequences required for packaging, assortment, transcription, or translation encompass the UTR and extend into the ORF (17)(18)(19)(20)(21). Experimental and computational evidence suggests inter-segment complementarity drives assortment of Reoviridae +RNAs, with shorter gene segments nucleating +RNA complexes that are packaged into assembling viral capsids (22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%